Summertime - Lynne S. Wilcox (Preventing Chronic Disease, 2004)
Dandelion Wine is a lyrical coming-of-age story set in Green Town, Illinois, in the early 20th century (1). Douglas Spaulding is 12 years old, and summertime has arrived. When its a new summer, you need new shoes. In fact, you need Royal Crown Cream-Sponge Para Litefoot Tennis Shoes. But Doug doesnt have the money. He bargains with Mr. Sanderson, the proprietor of the local shoe store: Soon as I get those shoes on, you know what happens? . . . Bang! I deliver your packages, pick up packages, bring your coffee, burn your trash, run to the post office, telegraph office, library! Youll see twelve of me in and out, in and out, every minute. Many readers older than 50 will recognize Doug. He may have a different name, he may want a bike instead of tennis shoes, he may like root beer instead of lemonade. Still, its summertime, and hes in 12 places all at once.